Liver cirrhosis first time presented with delirium unveiled as accidental secondary hypothermia - Malakar, Sayan; Sharma, Kailash Nath; Negi, Bhagwan Das; Sharma, Tarun; Sharma, Aradhna (Indian Journal of Case Reports, 2019)
Liver cirrhosis is a condition which is defined histopathologically but cannot be diagnosed clinically without any non-invasive tests. There are various etiologies of cirrhosis such as alcoholic liver disease, chronic viral hepatitis B, C, and non-alcoholic fatty liver diseases. Liver, not only function as an organ for detoxification, conjugation, and synthesis but also it regulates body heat. Cirrhosis patients thus are prone to body heat loss and hyperthermia. We present a case with undiagnosed liver cirrhosis patient, 1st time presenting with altered sensorium, revealed as accidental secondary hypothermia with ECG changes of hypothermia. The patient treated for hypothermia only after which she recovered.